Staging Evaluation and Response Criteria Harmonization (SEARCH) for Childhood, Adolescent and Young Adult Hodgkin Lymphoma (CAYAHL): Methodology statement. Issue 7 (18th January 2017) - Flerlage, Jamie E.; Kelly, Kara M.; Beishuizen, Auke; Cho, Steve; De Alarcon, Pedro A.; Dieckmann, Ute; Drachtman, Richard A.; Hoppe, Bradford S.; Howard, Scott C.; Kaste, Sue C.; Kluge, Regine; Kurch, Lars; et al.
Abstract: International harmonization of staging evaluation and response criteria is needed for childhood, adolescence, and young adulthood Hodgkin lymphoma. Two Hodgkin lymphoma protocols from cooperative trials in Europe and North America were compared for areas in need of harmonization, and an evidence‐based approach is currently underway to harmonize staging and response evaluations with a goal to enhance comparisons, expedite identification of effective therapies, and aid in the approval process for new agents by regulatory agencies.